Electronic Doping of Metal‐Organic Frameworks for High‐Performance Flexible Micro‐Supercapacitors. Issue 3 (25th November 2020) - He, Yafei; Yang, Sheng; Fu, Yubin; Wang, Faxing; Ma, Ji; Wang, Gang; Chen, Guangbo; Wang, Mingchao; Dong, Renhao; Zhang, Panpan; Feng, Xinliang
Abstract : The combination of high specific surface areas, well‐defined porous structures, and redox‐active sites renders the organic frameworks as promising electrode materials for next‐generation energy storage devices. Despite the recent advancements in the fabrication of conductive metal‐organic frameworks (MOFs), they generally require tedious synthesis procedures, which hinder their energy‐related applications. Herein, a doping strategy using electron acceptor molecules is demonstrated to tune the ohmic electrical conductivity of MOF thin‐film electrodes. For instance, the conductivity of MOF Cu3 (BTC)2 film is enhanced over 40 times after doping with 7, 7, 8, 8‐tetracyanoquinododimethane (TCNQ). Thereby, asymmetric in‐plane micro‐supercapacitors (MSCs) are constructed utilizing in situ‐grown TCNQ@Cu3 (BTC)2 as the cathode and activated carbon as the anode, which delivers remarkable areal capacitance of 95.1 mF cm −2 at a scan rate of 5 mV s −1, superior to those of the reported MSCs (0.1–50 mF cm −2 ). Moreover, the fabricated devices show long‐term stability with 94.1% capacitance retention up to 5000 charge‐discharge cycles at 10 mA cm −2 . The molecular doping engineering of organic framework materials with excellent electronic properties for energy storage and conversion applications is inspired. Abstract : An electronic doping strategy is demonstrated to tune ohmic electrical conductivity of metal‐organic framework thin‐film electrodes for high‐performance flexible microsupercapacitors. The fabricated device delivered a remarkable areal capacitance of 95.1 mF cm −2 at 5 mV s −1 . The molecular doping engineering of organic framework materials with excellent electronic properties for energy storage and conversion applications is inspired.